To unsee the sea : modern refugees on screen - Jurišić, Paula (Array, 2020)
This article provides a glimpse into the echo of the European refugee crisis in contemporary European cinema and the modes of narration deployed in representations of the phenomenon that is rapidly changing the European political and cultural landscape. The representation of the crisis seems to be bringing about a crisis of representation. Mainstream media refugee images are penetrating both the big screens and television production. Drama and victimhood are, consequently, inevitably becoming the dominant modes of narration (See Rosi’s Fuocoammare), but a growing number of filmmakers address the issue in rather creative ways, bravely experimenting with the nature of the cinematic event as a whole.